A Low Viral Dose in COVID-19 Patient: A Case Report - Li, Yajuan; Hu, Xianwei; Tu, Youhui; Wu, Tao; Wang, Bo; Ma, Huan; Zeng, Weihong; Zhao, Dan; Mengist, Hylemariam Mihiretie; Kombe, Arnaud John Kombe; Zheng, Meijuan; Xu, Yuanhong; et al. (Frontiers in Public Health, 2020)
SARS-CoV-2 outbreak has attracted global attention. Verifying the presence of viral RNA is the gold standard for the diagnosis of COVID-19. However, RT-qPCR diagnosis often fails to catch infected patients, because of inconsistent swab sample collection. Here we report a case that showed 5 consecutive negative and 1 low-viral- dose RT-qPCR results during illness spanning over twenty days. Clinical symptoms suggest SARS-CoV-2 infection with typical ground glass like a lung in computed tomography. SARS-CoV-2 infection was serologically confirmed by the presence of anti-SARS-CoV-2 specific antibodies in patients’ serum. Finally, a high level of protective IgG was produced after the patient recovered. Surprisingly, as a barber and a housewife staying at home for the first two weeks after the onset of illness, none of the close contacts were infected, showing a case of low viral load and low infectivity in this patient.